(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Andriani LT, Poromarto SH, Supyani, Purwanto E, Hadiwiyono. 2025. Characterization and biocontrol of Pantoea ananatis, the causal agent of rice bacterial leaf blight in Malang, Indonesia. Biodiversitas 26: 1537-1544. Disease outbreaks pose a significant obstacle to sustainable agricultural production. Two major diseases affecting rice crops are bacterial leaf blight and blast disease. Bacterial leaf blight caused by Pantoea ananatis is considered new, based on field observations, the cause of bacterial leaf blight is still Xanthomonas oryzae pv. oryzae. Research on P. ananatis is important to provide new knowledge about the causes of bacterial leaf blight other than X. oryzae pv. oryzae. The symptoms of bacterial leaf blight include yellowing and browning of the leaf, followed by drying, resulting in death of the leaf cells. The objectives of this study were to isolate the bacteria, identify them morphologically and molecularly, determine physiological characteristics and explore their biocontrol potential using rhizobacteria. Bacterial characterization was performed both morphologically and physiologically. This study determined the hypersensitive response of tobacco leaves, physiological and biochemical characteristics, pathogenicity tests, and molecular identification via 16S rRNA gene sequencing. The bacteria formed yellow colonies on yeast chalk dextrose agar at 36°C. Isolate was positive for indole and Levan tests, used citrate as a carbon source, and liquefied gelatin at low temperatures. The bacteria showed positive results in tobacco hypersensitivity and pathogenicity tests on paddy rice. Molecular identification results showed that the bacterial pathogen was identified as P. ananatis. The result of biocontrol potential test was shown that bacteria with the code UNS-R2 can control the pathogenic bacteria P. ananatis using spray method. These findings can be used as new knowledge about the types of leaf blight pathogens other than X. oryzae and their control alternatives to determine tactical steps in integrated crop management toward sustainable agriculture. This is the first report on the identification and characterization of P. ananatis in rice in Indonesia and the biocontrol potential using rhizobacteria.